TECHNOLOGICAL INNOVATIONS AND SCHOOL CONTEXT: REFLECTIONS REQUIRED - Darido, Maira da Cunha [UNESP]; Bizelli, Jose Luis [UNESP] (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2015)
In modern society technologies have played an important space exerting influences in different spheres. Today's young people are born immersed in the digital and virtual reality, which has changed the ways of learning, as well as to relate to the world. All this context has intensified the debate on the potential of ICT in education and training means. In this study, we sought to investigate the teachers' vision of ICT in the school environment, how they are being incorporated into the school and the limits and possibilities of the use of ICT in the learning process. Questionnaires were administered to 150 teachers who teach in high school in the state network of Sao Paulo teaching, but specifically in Piracicaba. Continuing, semi-structured interviews with a group of 8 directors were carried out so that there was a deepening on the issues raised by teachers in the questionnaire. The research brought to light important issues for discussion and referral measures striving to support public policies of integration of ICT in schools. Teachers spoke about the advantages and disadvantages of their use and the process of integration. It was observed that, despite efforts to implementation, there are still problems with infrastructure of schools, teacher training and working conditions.
Keywords: ICT; Teachers view; Public policy